Kualitas Tidur dan Tekanan Darah Sopir Angkot Lintas Bula-Ambon - Zulfikar Lating; Sahrir Sillehu; Abd Rijali Lapodi; Iswandi Fataruba (FORIKES, 2022)
Certain types of work are very influential on the rise of blood pressure. The increase in blood pressure in drivers can be caused by several factors including physical activity, stress due to work pressure, environment and lifestyle. Fatigue due to physical activity or excessive stress has a negative impact on the driver's sleep quality. The purpose of this study was to analyze the relationship between sleep quality and blood pressure of Bula-Ambon angkot drivers in 2021. The design of this study was cross-sectional. The respondents of this study were 35 respondents of Bula-Ambon angkot drivers who were selected using the total population sampling technique. Data were collected through filling out questionnaires at the Bula - Ambon angkot driver base, namely the Passo Transit base. Furthermore, the data were analyzed using the Chi-square test. The results of the analysis showed that the p-value was 0.000, so it was concluded that there was a relationship between sleep quality and blood pressure of the Bula-Ambon angkot drivers.Keywords: driver; sleep quality; blood pressure ABSTRAK Jenis pekerjaan tertentu sangat berpengaruh besar terhadap naiknya tekanan darah. Naiknya tekanan darah pada sopir dapat disebabkan oleh beberapa faktor antaranya adalah aktivitas fisik, stress karena tekanan kerja, lingkungan dan gaya hidup. Kelelahan akibat aktivitas fisik atau stress yang berlebihan berdampak negatif terhadap kualitas tidur sopir. Tujuan penelitian ini adalah untuk menganalisis hubungan antara kualitas tidur dengan tekanan darah sopir angkot lintas Bula-Ambon pada tahun 2021. Rancangan penelitian ini adalah cross-sectional. Responden penelitian ini adalah 35 responden sopir angkot Bula-Ambon yang dipilih dengan teknik total population sampling. Data dikumpulkan melalui pengisian kuesioner di pangkalan sopir angkot Bula - Ambon yaitu pangkalan Transit Passo. Selanjutnya data dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa nilai p adalah 0,000, sehinga disimpulkan bahwa ada hubungan antara kualitas tidur dengan tekanan darah sopir angkot lintas Bula - Ambon.Kata kunci: sopir; kualitas tidur; tekanan darah